Pendekatan Open-ended Terhadap Kemampuan Metakognitif Siswa: Alternatif Pembelajaran di Kurikulum 2013 - Lestari, Wahyu; Fatinatus Selvia; Rohmatul Layliyyah (At- Ta'lim : Jurnal Pendidikan, 2019)
The government through the Ministry of Education and Culture has carried out various new innovations in improving the quality of education in various levels of education units at the elementary, secondary and tertiary levels. One of them is through curriculum changes from KTSP to the Kurikulum 2013. In this curriculum there is new knowledge that must be raised in learning, namely metacognitive. But in its implementation, teachers lack the use of students’ metacognotive abilities. Of course in bringing up this metacognitive ability requires a learning approach. One of the approaches is open-ended, which refers to the principle that the process, results, and path to getting answers are all open. This article will discuss the literature review of the open-ended approach in generating students’ metacognitive abilities in learning. So that from the results of this literature review can be used as an alternative mathematics learning in the Kurikulum 2013.